The Impact of Mentoring and Scholarships on Teacher Candidates - Linda Gray Smith; Victoria N Seeger; Michael McBride; Timothy J Wall (Educational Considerations, 2024)
The study examines data from surveys and interviews with teacher candidates and local education mentors at a Midwestern university who were involved in a Grow Your Own program; this article focuses on results for the teacher candidates. Using data based on demographics, financial need, and academic performance, the researchers identified eight educator preparation candidates from under-represented backgrounds. Each teacher candidate was invited to receive an academic scholarship of $1,500 per semester for two terms, fall 2022 and spring 2023, with the understanding each scholarship recipient would be paired with a university mentor and an in-district mentor from one of two rural school districts with close proximity to the Midwest university. Teacher candidates were required to attend introductory meetings, professional learning, and culminating sessions in order to receive and retain the scholarship funds. Researchers sought to understand perceptions on mentoring, financial support, and professional development from the teacher candidates while investigating the impact of mentoring on retention. The qualitative case study included a pre- and post-survey for scholarship recipients. The scholarship recipients also participated in a focus group interview. Findings included the importance of the scholarship funds to the teacher candidates that went beyond financial implications, and being selected to participate made them “feel special.” The relationships formed with the university faculty and the local education mentors became a “network” allowing the teacher candidates to feel confident and valued; they became the educators they will continue to rely on throughout their careers. The professional development provided opportunities for participants to see, in real-time, the concepts that were discussed in abstract during their education courses. Key Words: mentoring teacher candidates, teacher preparation, relationships, grow your own
Keywords: Mentoring Teacher Candidates; Teacher Preparation; Relationships; Grow Your Own